2016
DOI: 10.1063/1.4963782
|View full text |Cite
|
Sign up to set email alerts
|

Improving the radiation hardness of graphene field effect transistors

Abstract: Ionizing radiation poses a significant challenge to the operation and reliability of conventional silicon-based devices. Here, we report the effects of gamma radiation on graphene field-effect transistors (GFETs), along with a method to mitigate those effects by developing a radiationhardened version of our back-gated GFETs. We demonstrate that activated atmospheric oxygen from the gamma ray interaction with air damages the semiconductor device, and damage to the substrate contributes additional threshold volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…A similar result has been reported for graphene, where gamma radiation was used to p-dope graphene. 37 Several reports have demonstrated that gamma radiation treatments modify the material properties by the self-controlled process and this characteristic effect can be used to develop materials with statistically stabilized and desired properties. 38,39 In order to gain a deep insight into the origin of the magnetization observed in the monolayer WS 2 , as shown in Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…A similar result has been reported for graphene, where gamma radiation was used to p-dope graphene. 37 Several reports have demonstrated that gamma radiation treatments modify the material properties by the self-controlled process and this characteristic effect can be used to develop materials with statistically stabilized and desired properties. 38,39 In order to gain a deep insight into the origin of the magnetization observed in the monolayer WS 2 , as shown in Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Of particular interest, however, is the effect of radiation on 2D materials. While radiation effects on the electrical properties of Graphene have been studied 23,24 , less is known about these effects on TMDs and other 2D materials 25 . In particular, no study investigates the effect of radiation on optical characteristics of 2D materials.…”
mentioning
confidence: 99%
“…The working principle is based on the induced lattice defects in graphene in response to ionizing radiation. These defects eventually shift the graphene towards a non-crystalline phase [ 31 ], in parallel with p-doping due to interaction with air molecules [ 21 , 22 , 32 ], thus decreasing the electron mobility and increasing the graphene’s resistivity. As shown in Figure 1 , two irradiated graphene sensors were connected to the RF ring oscillator transducer circuit to monitor the change in the oscillating frequency in response to the different radiation doses.…”
Section: Working Principlementioning
confidence: 99%
“…Along these lines, recent research has used graphene in detecting a wide range of radiation dosages from 1 to 20 kGy via physical changes in bandgap characteristics. Gamma-radiation-induced p-doping in graphene affects the graphene’s crystal structure and band properties by breaking the zero-gap property and introducing new vacancies into the lattice structure, affecting electron mobility and thus increasing resistivity and changing the electronic properties of the 2D material [ 21 , 22 ]. In our previous work, graphene was used to enhance the sensitivity of Schottky-junction low-bias radiation sensors by controlling the current passing into the fabricated junction made of n-Si/Pt/graphene and detecting the Schottky barrier’s height and width.…”
Section: Introductionmentioning
confidence: 99%